ANALISIS PENGARUH KEPUASAN PELAYAN NASABAH TERHADAP KINERJA BANK PADA BANK MANDIRI CABANG PALANGKA RAYA - Pamungkur Pamungkur (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
In order to promote competition, company should be able to provide its customers with satisfaction, for instance by giving products with better quality, affordable, better service than the competitors. Customers satisfaction or unsatisfaction becomes a national, global, industrial and service company trending topic. Customers satisfaction is considered by goods/service quality customers expect. Therefore, quality assurance is the main priority for every company, particularly now that is perceived as a competition excellence benchmark for company. This study aimed (a) to analyze the conformity between interest level of service components according to customers with the performance done by Bank Mandiri and (b) to analyze customers satisfaction on services provided so as to contribute the performance of Bank Mandiri to achieve good quality improvement by the stipulation of main priority. This study used a Qualitative data method by scoring, in calculation scale. A statement or question requiring alternative response, such as: very satisfied, satisfied, less satisfied, not satisfied at all, respectively with figures given 4 (four), 3 (three), 2 (two), and 1 (one). There are 2 types of data namely qualitative and quantitative data. Quantitative data is classified into discrete/nominal data and continue data. Nominal data are data that can only be classified individually, in discrete or categorical. These data were collected by calculation outcomes, for instance in a class, there are 50 students consisting of 30 males and 20 females. Study results suggested that factors becoming main priority or at Quadrant IV on cartesius diagram that should be performed as customers expectation among others: Teller attention to customers, all employees’ integrity in terms of servicing customers, waiting time in ATM queue, the presence of ATM machine, Interest Rate given by bank currently. Since those factors identify factors or attributes considered to have influenced customers service including components perceived crucial, however the management has not performed as customers expect, consequently, it is disappointing/unsatisfying